The effect of teacher teaching, learning methods and students’ perceptions on the student's learning achievement in Medan city - Limega Candrasa; Cia Cai Cen (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Learning achievement is something that cannot be separated from learning activities because learning achievement is the output of the learning process. Student achievement is influenced by two main factors, namely factors from within the student (Internal) and factors originating from outside the student or the environment (External). The research method used is quantitative data method. Qualitative research as a human instrument, serves to determine the focus of research, select informants as data sources, assess data quality, analyze data, interpret data and draw conclusions from the findings. The results of the study using t-test (partial) showed that the Teacher Teaching Method variable (X1) had an effect on the student achievement variable (Y), then the online learning method (X2) had an effect on student achievement (Y).